Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/app12041975
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Segmentation and Building Extraction from Airborne LiDAR Data with Multiple Return Using PointNet++

Abstract: Light detection and ranging (LiDAR) data of 3D point clouds acquired from laser sensors is a crucial form of geospatial data for recognition of complex objects since LiDAR data provides geometric information in terms of 3D coordinates with additional attributes such as intensity and multiple returns. In this paper, we focused on utilizing multiple returns in the training data for semantic segmentation, in particular building extraction using PointNet++. PointNet++ is known as one of the efficient and robust de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Hyeongmo Gu and Seungyeon Choo used façade datasets and deep learning to automatically mark façade data and effectively generate large-scale data sets to understand the characteristics of the street [12]. Young-ha Shin et al used PointNet++ to extract and segment buildings and found that the two echoes of the laser pulse could be fully identified and removed in said buildings [13]. The systems proposed in the thesis of Shi-Jinn Horng and Pin-siang Huang can identify the different states of a product with effective identification of the products [14].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Hyeongmo Gu and Seungyeon Choo used façade datasets and deep learning to automatically mark façade data and effectively generate large-scale data sets to understand the characteristics of the street [12]. Young-ha Shin et al used PointNet++ to extract and segment buildings and found that the two echoes of the laser pulse could be fully identified and removed in said buildings [13]. The systems proposed in the thesis of Shi-Jinn Horng and Pin-siang Huang can identify the different states of a product with effective identification of the products [14].…”
Section: Background and Related Workmentioning
confidence: 99%
“…To verify the accuracy of 3D segmentation process, we employed global accuracy metric [24], which is defined as below:…”
Section: Feature Extractionmentioning
confidence: 99%